Acceleration effects of microbial inoculum on palm oil mill organic waste composting. - Chin, Nyuk Ling; Yeoh, Chui Yen; Tan, C. S.; Ooi, H. S. (2011)
ABSTRACT The acceleration effects of inoculum in composting of empty fruit bunches were investigated. Composting of empty fruit bunches fibres in two sizes, 4 cm and 2 cm length, were treated with microbial inoculum consisting of Agromonas, Aspergillus, Azotobacter, Bacillus, Celhdomonas, Chaetomium, Clostridium, Coprinus, Microbispora, Penicillium, Pseudomonas, Thermoactinomyces, Trichoderma and Trichurus in separate laboratory scale in-vessel of 30 liters volume. A control without inoculum with 4 cm length empty fruit bunches was also conducted in parallel. The compost piles were shift-turned weekly. Parameters such as moisture content, temperature, pH, and electrical conductivity were used to monitor the composting processes. The carbon-nitrogen ratio, UV-vis spectrophotometer test, and germination test were used to assess the maturity of compost. The results showed that the inoculum was effective in reducing the C/N ratio by 54% compared to control 46% and rapidly increasing the UV-vis absorption ratio in first three weeks. By using functional microbes, the composting of empty fruit bunches was reduced to 5 weeks compared to 9 weeks for those without inoculation. The acceleration effect was more prominent for the 2 cm length samples.